2013
DOI: 10.1371/journal.pone.0073189
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic Variation in the Plant Pathogenic Bacterium Acidovorax citrulli

Abstract: Acidovorax citrulli causes bacterial fruit blotch (BFB) of cucurbits, a disease that threatens the cucurbit industry worldwide. Despite the economic importance of BFB, little is known about pathogenicity and fitness strategies of the bacterium. We have observed the phenomenon of phenotypic variation in A. citrulli. Here we report the characterization of phenotypic variants (PVs) of two strains, M6 and 7a1, isolated from melon and watermelon, respectively. Phenotypic variation was observed following growth in r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 63 publications
1
15
0
Order By: Relevance
“…These results led us to suggest that the mucoid and transparent variants produced by P. viridiflava are actually programmed mutants rather than bona fide phase variants. In contrast with our results, the phytopathogenic bacteria R. solanacearum , A. citrulli and X. oryzae have been reported to restore their EPS‐producing aggressive phenotype after growth in host plants (Poussier et al ., ; Rajeshwari and Sonti, ; Shrestha et al ., ), suggesting that P. viridiflava displays a different phenomenon from that of other plant‐pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…These results led us to suggest that the mucoid and transparent variants produced by P. viridiflava are actually programmed mutants rather than bona fide phase variants. In contrast with our results, the phytopathogenic bacteria R. solanacearum , A. citrulli and X. oryzae have been reported to restore their EPS‐producing aggressive phenotype after growth in host plants (Poussier et al ., ; Rajeshwari and Sonti, ; Shrestha et al ., ), suggesting that P. viridiflava displays a different phenomenon from that of other plant‐pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 98%
“…oryzae , occurring during the stationary phase in in vitro culture, deficient in EPS production, are less aggressive, although they maintain a certain level of pathogenicity (Rajeshwari and Sonti, ). Recently, phenotypic variations have also been described in Acidovorax citrulli , the causal agent of bacterial fruit blotch of cucurbits (Shrestha et al ., ). The authors demonstrated that phenotypic variants of A. citrulli are different from the parental wild‐types with regard to biofilm formation, swimming mobility and aggressiveness on melon plants.…”
Section: Introductionmentioning
confidence: 97%
“…Past reports indicate that colony morphology of A. citrulli was in contact with twitching motility [29,30]. To examine the role of light on twitching motility of A. citrulli, wild-type Aac5 was cultured and incubated on nutrient agar plates in the light or dark for 48 h. The results showed that strain Aac5 showed stronger twitching motility when cultured in the dark compared to that under light conditions ( Fig.…”
Section: Light Supresses Twitching Motility Of a Citrullimentioning
confidence: 88%
“…Primary dysf -/myoblasts were prepared from hindlimb muscles as described in section 2.6 and plated at a density of 2 x 10 3 cell/cm 2 on glass coverslips (Bar Naor Ltd., Ramat Gan, Israel) in 96-well plates (Thermo Fisher Scientific, Waltham, MA), in DMEM containing 20% FBS at 37.5°C with humidified atmosphere and 5% CO2 in air. The cells were induced to 8 differentiate by changing the medium to DMEM containing 2% horse serum for 24 h followed by a medium change back to 20% FBS in DMEM for 2 h. The cells were then treated, or not, with 10 nM halofuginone for another 24 h, and prepared for SEM as previously described [39].…”
Section: Cell Preparation For Scanning Electron Microscopy (Sem)mentioning
confidence: 99%
“…">Cell preparation for scanning electron microscopy (SEM)Primary dysf -/myoblasts were prepared from hindlimb muscles as described in section 2.6 and plated at a density of 2 x 10 3 cell/cm 2 on glass coverslips (Bar Naor Ltd., Ramat Gan, Israel) in 96-well plates (Thermo Fisher Scientific, Waltham, MA), in DMEM containing 20% FBS at 37.5°C with humidified atmosphere and 5% CO2 in air. The cells were induced to 8 differentiate by changing the medium to DMEM containing 2% horse serum for 24 h followed by a medium change back to 20% FBS in DMEM for 2 h. The cells were then treated, or not, with 10 nM halofuginone for another 24 h, and prepared for SEM as previously described [39].Cells were fixed in PBS containing 2% paraformaldehyde, 2% (v/v) glutaraldehyde and 1% (w/v) sucrose for 1 h at room temperature, and treated with PBS containing 1% (v/v) osmium tetraoxide and 1% sucrose for another 1 h. The cells were then rinsed and dehydrated using increasing ethanol concentrations of 25%, 50%, 75%, 95% and 100%. The samples were dried in a critical point dryer (Bal-Tec C.P.D 030, BAL-TEC AG, Blazers, Germany) by displacing the alcohol with liquid CO2 and then releasing the CO2.…”
mentioning
confidence: 99%